Fibromyalgia as a Heterogeneous Condition: Subgroups of Patients Based on Physical Symptoms and Cognitive-Affective Variables Related to Pain. (18th May 2021) - Martínez, M. Pilar; Sánchez, Ana I.; Prados, Germán; Lami, María J.; Villar, Beatriz; Miró, Elena
Abstract: Fibromyalgia (FM) is a chronic syndrome characterized by heterogeneous clinical manifestations, and knowing this variability can help to develop tailored treatments. To understand better the heterogeneity of FM the present cross-sectional study analyzed the role of several physical symptoms (pain, fatigue and poor sleep quality) and cognitive-affective variables related to pain (pain catastrophizing, pain vigilance, self-efficacy in pain management, and pain acceptance) in the configuration of clinical profiles. A sample of 161 women with FM fulfilled an interview and several self-report measures to explore physical symptoms, cognitive-affective variables, disability and psychopathology. To establish FM groups a hierarchical cluster analysis was performed. The findings revealed three clusters that differed in the grouping variables, Wilks' λ = .17, F (14, 304) = 31.50, p < .001, ηp 2 = .59. Group 1 ( n = 72) was characterized by high physical and psychological affectation, Group 2 ( n = 19) by low physical affectation and high pain self-efficacy, and Group 3 ( n = 70) by moderate physical affectation and low pain catastrophizing. The external validation of the clusters was confirmed, Wilks' λ = .72, F (4, 314) = 14.09, p < .001, ηp 2 = .15, showing Group 1 the highest levels of FM impact and psychopathological distress. Considering the distinctive clinical characteristics of each subgroup therapeutic strategies addressed to the specific needs of each group were suggested. Assessing FM profiles may be key for a better understanding and approach of this syndrome.